JURIDICAL REVIEW OF ARTICLE 112 OF THE REGULATION OF THE MINISTER OF AGRARIAN AFFAIRS/HEAD OF THE NATIONAL LAND AGENCY NUMBER 3 OF 1997 REGARDING THE LEGAL CONSEQUENCES OF THE POSITION OF THE EXECUTOR OF A WILL IN A DEED OF GRANT DUE TO A WILL IF THE EXE - Sari, Putri Nurmalita; Handayani , I Gusti Ayu Ketut Rachmi; Tuhana , Tuhana (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
A testamentary gift is a special testamentary stipulation, whereby the person who bequeaths to one or more persons gives certain items from their inherited assets or provides items of a certain type, such as, for example, all their movable or immovable items, or grants rights use the proceeds from all or part of his inheritance. According to the provisions of Article 112 paragraph (1) a point 3 letter b Regulation of the Minister of State for Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 concerning Provisions for Implementing Government Regulation Number 24 of 1997 concerning Land Registration (PMNA/KBPN No.3/1997), states that